2021
DOI: 10.21203/rs.3.rs-753486/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infrared Nanoscopy and Tomography of Intracellular Structures

Abstract: The few microscopic techniques that simultaneously gather morphological and chemical data often rely on the use of specific markers. To eliminate this flaw, we have developed a method of examining cellular cross sections using the imaging power of scattering-type scanning near-field optical microscopy and Fourier-transform infrared spectroscopy at a spatial resolution far beyond the diffraction limit. Herewith, nanoscale surface and volumetric chemical imaging is performed using the intrinsic contrast generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…In fact, several s-SNOM studies have already investigated slices microtomed from the bulk sample, such as hair [93], silk [108], and cellulose materials [125]. Recently, Kanevche et al has reported s-SNOM imaging of 100 nm-thick cellular cross-sections of eukaryotic and prokaryotic cells, and a 3D tomogram with 20-nm IR resolution was composed [126]. The smooth combination of AFM-based nano-IR techniques with advanced microtome methodology will streamline the discovery of spatial-temporal correlations in life-relevant cells and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several s-SNOM studies have already investigated slices microtomed from the bulk sample, such as hair [93], silk [108], and cellulose materials [125]. Recently, Kanevche et al has reported s-SNOM imaging of 100 nm-thick cellular cross-sections of eukaryotic and prokaryotic cells, and a 3D tomogram with 20-nm IR resolution was composed [126]. The smooth combination of AFM-based nano-IR techniques with advanced microtome methodology will streamline the discovery of spatial-temporal correlations in life-relevant cells and tissues.…”
Section: Discussionmentioning
confidence: 99%